Doping : proceedings of an international seminar - Schaepdryver, A. de; Hebbelinck, M. (Symposium Publications Division, Pergamon Press, 1965)
Doping brings together the proceedings of an International Seminar on Doping organized by the Research Committee of UNESCO's International Council of Sport and Physical Education and held in Belgium in May 1964. The papers explore the doping problem in sports and physical education using a multidisciplinary approach, with emphasis on the pharmacological, biochemical, psychological, ethical, social, and juridical aspects of doping. This volume is comprised of 13 chapters and begins with an overview of the general and pharmacological aspects of doping, along with the essential points in the obje.